Machado de Assis, portraitist - Rosa, Victor da [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2018)
This paper intends to analyze some aspects of Machado de Assis' fiction drawing on the notion of pose, which was suggested by the discussions on Photography in the 19th century: poses hall was the name given to the photographic studios that emerged right after the invention of the daguerreotype, in 1839. The paper discusses Machado's critique on landscape, a genre of Photography and Art, as well as Silvio Romero's conclusion that Machado was a bad portraitist, highlighting the value of such analyses. Finally, we try to show how the author privileged the investigation of the hall and the sociability, as defined by Georg Simmel, as well as coquetismo [coquetry] and other forms of appearance. We also attempt to analyze these aspects from the point of view of characters including Conselheiro Aires and short stories such as Teoria do Medalhao ['Theory of the Medallion].
Keywords: Machado de Assis; pose; portrait; photography